2008
DOI: 10.1111/j.1745-4549.2008.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Amylolytic Lactic Acid Bacteria Fermentation of Maize–cowpea Ogi

Abstract: The effect of starter cultures Lactobacillus plantarum (A6), Lactobacillus fermentum (OgiE‐1) and natural inoculum (NI) on some physicochemical properties of cofermented maize–cowpea (CMCO) was investigated. Crude protein, lipid, ash, crude fiber, carbohydrate energy and utilizable energy because of protein contents of CMCO fermented with A6 (A6MC), OgiE‐1 (OGMC) and NI (NIMC) are 12.46–13.74%, 3.58–4.96%, 1.06–1.85%, 3.06–4.62% and 66.81–68.30%, 355.26–363.2 kcal/100 g and 7.43–9.14%, respectively. Mineral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
2
6
1
Order By: Relevance
“…Early production of acid and the consequent rise in TA is important to avoid proliferation of undesirable organisms. The increase of TA with fermentation time is in agreement with the report that TA increased with fermentation time in co-fermentation of maize/cowpea using starter cultures [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Early production of acid and the consequent rise in TA is important to avoid proliferation of undesirable organisms. The increase of TA with fermentation time is in agreement with the report that TA increased with fermentation time in co-fermentation of maize/cowpea using starter cultures [20].…”
Section: Discussionsupporting
confidence: 92%
“…pH of co-fermented mixture dropped from about 7.0 to 3.8 within the first 24hr then rose to 5.0, 4.5 at 48 hours and 72 hours respectively (Table 1), that of fermented maize decreased from about 6.5 to 5.0, 5.5 and 4.0 at 24hours, 48hours and 72hours respectively. Decrease in pH of co-fermented maize/cowpea with fermentation time had been reported [20]. Titratable acidity (TA) increased from 0.0135mg/g to 0.17mg/g for fermented maize and that of co-fermented samples increased from 0.014 mg/g to 0.153mg/g.…”
Section: Ph and Titratable Acidity (Ta)mentioning
confidence: 81%
“…Furthermore, hydrolysis leads to the production small molecule carbohydrates from these larger carbohydrates, and these small molecule carbohydrates favorably benefit the rheological properties of corn flour [27] and also make it easier to form corn dough. Oyarekua et al [28] also observed that lactic acid bacteria hydrolyzed starch molecules in their studies on fermented oji-bread.…”
Section: Corn Starch Molecular Structurementioning
confidence: 92%
“…Moreover, certain polyphenolic pigments present in pericarp, alurone and endosperm regions of the pearl millet seeds impart undesirable grey color and taste to its products (McDonough and Rooney 1989). However, processing, e.g., fermentation (Oyarekua et al 2008) and dehulling, has been shown to reduce the protein, polyphenols and phytic acid contents for millet cultivars, and increase vitro protein digestibility (Akingbala 1991;El Hag et al 2002). Moreover, processing methodologies like soaking, germination and heat treatment are used to reduce the antinutritional factors (Masud et al 2007).…”
Section: Introductionmentioning
confidence: 99%